2015
DOI: 10.1080/13691058.2014.990518
|View full text |Cite
|
Sign up to set email alerts
|

Female streetwalkers' perspectives on migration and HIV/STI risks in a changing economic and social environment: a qualitative study in Shanghai, China

Abstract: China's 30-year economic boom has created a unique social and economic market for commercial sex, as well as for a workforce of migrant women from rural China. This qualitative study explores the impact of the rapidly changing social and economic environment on migration patterns, sexually transmitted infection (STI) knowledge, STI risk behaviours, and health beliefs among female streetwalkers in Shanghai. Qualitative data were collected in 2010 through semi-structured in-depth interviews with 16 streetwalkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…We focus on Chinese SBSW since much of the research on violence against sex workers has been carried out in developed Western countries such as the United States, England, and Canada [ 3 , 6 , 60 , 61 ]. Additionally, the recent expansion of commercial sex markets in developing countries, such as Thailand, India, and China, has incentivized researchers to shift their study settings [ 40 , 41 , 62 67 ]. China, in particular, has experienced a considerable growth in the prostitution sector over the past three decades [ 40 , 41 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on Chinese SBSW since much of the research on violence against sex workers has been carried out in developed Western countries such as the United States, England, and Canada [ 3 , 6 , 60 , 61 ]. Additionally, the recent expansion of commercial sex markets in developing countries, such as Thailand, India, and China, has incentivized researchers to shift their study settings [ 40 , 41 , 62 67 ]. China, in particular, has experienced a considerable growth in the prostitution sector over the past three decades [ 40 , 41 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the recent expansion of commercial sex markets in developing countries, such as Thailand, India, and China, has incentivized researchers to shift their study settings [ 40 , 41 , 62 67 ]. China, in particular, has experienced a considerable growth in the prostitution sector over the past three decades [ 40 , 41 , 67 ]. Hong and colleagues (2014) recently examined rates of both CIV and IPV among Chinese female sex workers and found high rates of both—nearly sixty percent had experienced IPV and forty-five percent reported CIV.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of 35 years to define mid-age FSWs was based on the findings from our qualitative studies conducted in the three sites [31] and from other reports [30, 36]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, about 530 million people have genital herpes and 290 million women have human papillomavirus. On the other hand, about 110,000 deaths have been attributable to STIs in the world [5].…”
Section: Introductionmentioning
confidence: 99%
“…The studies showed that despite high risk of STIs among FSWs, rate of condom use is not high [11,12]. Several epidemiological studies have reported different factors which effect on the use of condoms among female sex workers [5,13,14]. However, the results reported by the studies are inconsistent.…”
Section: Introductionmentioning
confidence: 99%